2004
DOI: 10.1007/978-94-007-0983-6_23
|View full text |Cite
|
Sign up to set email alerts
|

Outbreeding depression in hybrids between spatially separated pink salmon, Oncorhynchus gorbuscha, populations: marine survival, homing ability, and variability in family size

Abstract: Hybridization between distinct populations of salmon can cause fitness loss (outbreeding depression), and may result in reduced survival. The erosion of fitness-related traits such as homing ability and change in family size distribution may underlie reduced survival. Outbreeding depression was investigated in two independent experiments that made hybrids between geographically separated and genetically divergent pink salmon populations. Control crosses were made from male and female Auke Creek (Southeast Alas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 36 publications
2
53
1
Order By: Relevance
“…The fact that artificially selected brook charr are intensively used for stocking wild populations raises the issue of potentially negative consequences associated with reduction in genomic integrity and adaptative capacity of wild populations (Leary et al 1983;Gharrett et al 1999;Gilk et al 2004;Roberge et al 2006). For example, it has been shown in Atlantic salmon that genetic introgressive hybridization between farmed and wild fish substantially alters the genetic control of gene transcription within natural populations.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that artificially selected brook charr are intensively used for stocking wild populations raises the issue of potentially negative consequences associated with reduction in genomic integrity and adaptative capacity of wild populations (Leary et al 1983;Gharrett et al 1999;Gilk et al 2004;Roberge et al 2006). For example, it has been shown in Atlantic salmon that genetic introgressive hybridization between farmed and wild fish substantially alters the genetic control of gene transcription within natural populations.…”
Section: Discussionmentioning
confidence: 99%
“…If it has positive fitness consequences (e.g., if both populations were highly inbred before hybridization), it is referred to as hybrid vigor or heterosis. In most cases, outbreeding depression occurs when populations are separated at the species or subspecies levels, having been isolated for thousands of generations, though several studies have observed outbreeding depression within a single species of copepods in neighboring tidal pools [204][205][206] and among breeding stocks of salmon [207][208][209]. Heterosis is expected when small, inbred populations meet and hybridize.…”
Section: Outbreeding Depression Heterosis and Genomic Coadaptationmentioning
confidence: 99%
“…The genetic introgression of farmed escapees into native populations (Glover et al 2012) can lead to reduced overall fitness of wild populations (Fleming et al 2000, Gilk et al 2004, Tymchuk et al 2007) and competition for food and habitat (Jonsson & Jonsson 2006, Šegvić-Bubić et al 2011a. Post-escape behaviour of coldwater-aquaculture species, such as Atlantic salmon Salmo salar or Atlantic cod, has been extensively studied (Olsen & Skilbrei 2010, Skilbrei 2010, Chittenden et al 2011, Zimmermann et al 2013).…”
Section: Introductionmentioning
confidence: 99%